2010
DOI: 10.1038/onc.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Proton-assisted amino-acid transporters are conserved regulators of proliferation and amino-acid-dependent mTORC1 activation

Abstract: The PI3-kinase (PI3K)/Akt and downstream mammalian target of rapamycin complex 1 (mTORC1) signalling cascades promote normal growth and are frequently hyperactivated in tumour cells. mTORC1 is also regulated by local nutrients, particularly amino acids, but the mechanisms involved are poorly understood. Unexpectedly, members of the proton-assisted amino acid transporter (PAT or SLC36) family emerged from in vivo genetic screens in Drosophila as transporters with uniquely potent effects on mTORC1-mediated growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 47 publications
(71 reference statements)
7
166
0
Order By: Relevance
“…Other transporters included several members of the uptake organic anion transporting polypeptides (OATP) family (SLC21/SLCO) such as SLCO1B1/OATP1B1, SLCO2B1/OATP2B1, and SLCO1B3/OATP1B3, which are known to transport statins, antibiotics, chemotherapeutics, antihistaminic drugs, and diuretics (König, Müller & Fromm, 2013). In addition, the intracellular proton‐assisted amino acid transporter 1 PAT1/SLC36A1, which is an essential component of the amino acid‐sensing engine that drives mTORC1 activation from late endosomes and lysosomes, was included (Heublein et al., 2010). Several zinc‐containing matrix‐degrading endopeptidases (MMP‐1, MMP‐2, MMP‐3), which are known regulators of tissue remodeling in aging and cancer, were also included in the selected list of metformin targets.…”
Section: Resultsmentioning
confidence: 99%
“…Other transporters included several members of the uptake organic anion transporting polypeptides (OATP) family (SLC21/SLCO) such as SLCO1B1/OATP1B1, SLCO2B1/OATP2B1, and SLCO1B3/OATP1B3, which are known to transport statins, antibiotics, chemotherapeutics, antihistaminic drugs, and diuretics (König, Müller & Fromm, 2013). In addition, the intracellular proton‐assisted amino acid transporter 1 PAT1/SLC36A1, which is an essential component of the amino acid‐sensing engine that drives mTORC1 activation from late endosomes and lysosomes, was included (Heublein et al., 2010). Several zinc‐containing matrix‐degrading endopeptidases (MMP‐1, MMP‐2, MMP‐3), which are known regulators of tissue remodeling in aging and cancer, were also included in the selected list of metformin targets.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that amino acid transporters (AATs) played important roles in the absorption process of AAs and are important nutrient sensing molecules that play an important role in mTOR signaling pathways (Edinger, 2007). A recent study found that only a portion of the AAT was involved in regulating mTOR activation and caused mRNA translation (Heublein et al, 2010). In ruminants, a role of mTOR in the regulation of milk protein synthesis in the mammary glands has also been highlighted (Burgos et al, 2010;Toerien et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This transporter could play a role in mTORC1 activation in an amino acid-dependent manner (Heublein et al 2010). Knockdown of PAT1 in MCF-7 cells led to decreased S6K and 4E-BP-1 phosphorylation (Heublein et al 2010). Two membrane transporters, SLC7A5 and SLC3A2, were also shown to be required for mTORC1 activation (Nicklin et al 2009).…”
Section: Activation Of Mtorc1mentioning
confidence: 99%
“…In the lysosomes, the amino acid transporter PAT1 (protonassisted amino acid transporter 1; SLC36A1) is abundant and has been described as a lysosomal amino acid transporter (Russnak et al 2001). This transporter could play a role in mTORC1 activation in an amino acid-dependent manner (Heublein et al 2010). Knockdown of PAT1 in MCF-7 cells led to decreased S6K and 4E-BP-1 phosphorylation (Heublein et al 2010).…”
Section: Activation Of Mtorc1mentioning
confidence: 99%